Evaluation of allogeneic bone marrow-derived mesenchymal stem cells for use in equine joints: in vitro to preclinical evaluation - Colbath, Aimee, author; Goodrich, Laurie, advisor; Dow, Steven, advisor; McIlwraith, Wayne, committee member; Schenkel, Alan, committee member; Nakamura, Nori, committee member (Colorado State University. Libraries, 2019)
Joint disease is prominent in the equine population and horses provide a highly translational model for human joint disease. Mesenchymal stem cells (MSCs) have been investigated as a treatment of musculoskeletal disease in the horse with autologous MSCs showing promise as a treatment of desmitis, tendonitis and joint disease including meniscal injury and osteoarthritis. However, the culture expansion of autologous MSCs is both labor intensive and time consuming with an average expansion time of 2-4 weeks. Allogeneic MSCs would offer multiple potential advantages over autologous MSCs use including timing of treatment, potential for characterization, and selection of donors for desired stem cell characteristics. The safety of allogeneic MSCs must be established prior to clinical use. Allogeneic MSCs have been evaluated in vitro and in vivo, but rarely have allogeneic MSCs been directly compared with autologous MSCs. In addition, pre-clinical models must control for the large variability present in individual horses' reactions to joint injections as well as the variability in how different joints react to intra-articular treatments. Further, the safety of allogeneic MSCs must be examined in both the normal joint and inflammatory joint as MSCs may react to the joint environment. The goals of the research described in this dissertation were to directly compare the immune suppressive ability of autologous and allogeneic bone marrow-derived MSCs (BMDMSCs) in vitro, and directly compare both the normal and inflamed joint response to autologous and allogeneic BMDMSCs in vivo. In the first part of this work we compared the immune suppressive properties of allogeneic and autologous BMDMSCs in vitro. No difference was detected between the ability of allogeneic versus autologous BMDMSCs to suppress lymphocytes in modified mixed lymphocyte reactions. This work also established prostaglandin E2 as an important mediator of immune suppression used by allogeneic BMDMSCs. Following in vitro studies, two preclinical, in vivo studies were performed. In the first study, allogeneic and autologous BMDMSCs were administered into clinically normal, contralateral, metacarpophalangeal joints. No difference was detected in the clinical or cytological response of the normal equine joint to allogeneic versus autologous BMDMSCs. After establishing the response of the equine tibiotarsal joint to recombinant IL-1β (rIL-1β), an additional in vivo study was conducted to determine the inflamed joint response to allogeneic versus autologous BMDMSCs. In this study, no difference was detected in synovial fluid parameters, subjective lameness, or joint effusion between the inflamed joint response to allogeneic versus autologous BMDMSCs. In addition, no decrease in joint inflammation was detected as a result of autologous or allogeneic BMDMSC administration. The work described in this dissertation has improved our understanding of the equine joint response to allogeneic and autologous BMDMSCs. Further, it supports future exploration into the use of allogeneic BMDMSCs for musculoskeletal disease in the horse. Specifically, this work should be followed with a direct comparison of the efficacy of allogeneic versus autologous BMDMSCs for joint disease in the horse.
Keywords: bone marrow; horse; stem cell; equine; allogeneic; joint